Pre-Hospital and In-Hospital Management of an Abdominal Impalement Injury Caused by a Tree Branch - So Ra Ahn; Joo Hyun Lee; Keun Young Kim; Chan Yong Park (Journal of Trauma and Injury)
In South Korea, most patients who visit trauma centers with abdominal injuries have blunt trauma, and penetrating injuries are relatively rare. In extremely rare cases, some patients are admitted with a long object penetrating their abdomen, and these injuries are referred to as abdominal impalement injuries. Most cases of impalement injuries lead to fatal bleeding, and patients often die at the scene of the accident. However, patients who survive until reaching the hospital can have a good prognosis with optimal treatment. A 68-year-old female patient was admitted to the trauma center with a 4-cm-thick tree branch impaling her abdomen. The patient was transported by a medical helicopter and had stable vital signs at admission. The branch sticking out of the abdomen was quite long; thus, we carefully cut the branch with an electric saw to perform computed tomography (CT). CT revealed no signs of major blood vessel injury, but intestinal perforation was observed. During laparotomy, the tree branch was removed after confirming that there were no vascular injuries, and enterostomy was performed because of extensive intestinal injury. After treating other injuries, the patient was discharged without any complications except colostomy. Abdominal impalement injuries are treated using various approaches depending on the injury mechanism and injured region. However, the most important consideration is that the impaled object should not be removed during transportation and resuscitation. Instead, it should only be removed after checking for injuries to blood vessels during laparotomy in an environment where injury control is possible.